"All seems dreary, savage and desert": Janet Schaw's Journal of a Lady of Quality and American dystopia. Issue 4 (1st October 2016) - Van Netten Blimke, Linda
Abstract : Journal of a Lady of Quality (1774–1775) recounts Janet Schaw's journey to the West Indies, North Carolina and Lisbon during the turbulent years leading up to the American Revolution. This article considers Schaw's dystopic representation of America and the American colonists as a deliberate revision of common utopian visions and as a strategy to interrupt the sympathetic exchange between Britain and its American colonies. Positioned as a witness to the burgeoning Revolution, Schaw's transatlantic travels allowed her to engage directly with the political ideologies shaping and emanating from the colonial crisis. In order to facilitate her British audience's capacity to imagine American colonists as legitimate enemies rather than as loyal countrymen, she portrays American colonists both as irremediably foreign and as inherently violent. Her revision supports an aggressive British military response against the American colonists, which she believes is the only method by which Britain will retain its overseas Empire.